Sejaran dan Prospek Demokrasi - dadang supardan (Sosio-Didaktika: Social Science Education Journal, 2015)
This article was written for the anxiety of the phenomenon of the rise of the idea of ​​democracy as if change is to be erratic form of government, not driven by reason and rational needs. That since its inception, the idea of ​​democracy increasingly widespread after experiencing various historical events, especially when the formulation of the American Constitution in 1776 and the French Revolution of 1789. The democratic system is becoming more popular among followers of republicanism and is a critique of the dominance of the monarchy system in Europe. Nowadays, democracy can be seen as a ‘product’ as that term is defined previously as a ‘source of power’ rather than as ‘a method of governance’. Despite modern democracy is a complex device, but logic is expressed seem to contain a single principles. That democracy contains elements of popular participation, majority rule, minority protection, individual freedom, freedom guaranteed by law, participation in policy formulation at all levels, as well as equality. However, democracy is not without flaws, both conceptually mapun practice, given the many democracies that do not accommodate the interests of the sovereignty of the environment (ecocracy). Permalink/DOI: http://dx.doi.org/10.15408/sd.v2i2.2811